A meta-analysis of the influence of body mass index on the clinicopathologic progression of papillary thyroid carcinoma. Issue 32 (13th August 2021) - Cui, Ningning; Sun, Qian; Chen, Li
Abstract: Background: Papillary thyroid carcinoma (PTC) incidence has been increasing worldwide. Obesity, that is, having a high body mass index, is associated with the incidence of several cancers including colon, breast, esophageal, and kidney cancer. However, the association between obesity and the clinical features of PTC is still unknown. This study aimed to determine the impact of obesity on the clinical features of PTC. Method: A database search was conducted for articles published up to 2020 on obesity and clinical features of PTC. Data were extracted from articles that met the meta-analysis inclusion criteria. Results: A total of 11 retrospective cohorts and 11, 729 patients were included. Obesity was associated with the following variables in PTC patients: older age (difference in means = 1.95, 95% confidence interval [CI] 0.16–3.74, P = .03), male sex (odds ratio [OR] = 3.13, 95%CI 2.24–4.38, P < .00001), tumor size ≥1 cm (OR = 1.34, 95%CI 1.11–1.61, P < .002), multifocality (OR = 1.54, 95%CI 1.27–1.88, P < .0001), extrathyroidal extension (OR = 1.78, 95%CI 1.22–2.59, P = .003) and advanced tumor, node, metastasis stage (OR = 1.68, 95%CI 1.44–1.96, P < .00001). Preoperative serum thyroid-stimulating hormone level (difference in means = 0.09, 95%CI 0.35–0.52, P = .70), Vascular invasion (OR = 0.84, 95%CI 0.56–1.26, P = .41), lymph node metastasis (OR = 1.07, 95%CI 0.87–1.32, P = .50), distant metastasis (OR = 1.14, 95%CI 0.64–2.04, P = .66), and recurrence (OR = 1.45, 95%CI 0.97–2.15, P = .07) were not associated with obesity. Conclusion: Obesity was associated with several poor clinicopathologic prognostic features: older age, male gender, tumor size ≥1 cm, extrathyroidal extension, multifocality, and advanced tumor/node/metastasis stage. However, thyroid-stimulating hormone level, vascular invasion, lymph node metastasis, distant metastasis, and recurrence were not associated with obesity in PTC. Abstract : Supplemental Digital Content is available in the text